(untitled) (Zien Journal of Social Sciences and Humanities, 2022)
Wrestling is a sport in which two athletes compete one-on-one in accordance with the established rules. The art of wrestling has been known in many nations since ancient times. Wrestling is especially popular in Greece and has been a regular feature of the ancient Olympics. Various forms of national wrestling exist in Greece, Italy, Japan, Turkey, Iran, Afghanistan, Russia, Uzbekistan, Georgia, Armenia, Azerbaijan, Kazakhstan and other countries.